An analysis of the spatial and temporal changes on the Jakobshavn Glacier (Greenland) using remote sensing data - Olszewska, Katarzyna; Borowiec, Natalia (Geology, Geophysics and Environment, 2021)
This article presents the problem of climate warming and the effect of melting ice caps. The problem of climate warming is discussed in two stages. In the first stage, the factors affecting global warming are discussed in detail and the effects and risks of ablation extensively described. Analyses were conducted on data available online from NASA and Carbon Dioxide Information Analysis Center. The Greenland area (Jakobshavn Glacier) was selected to visualize glacier calving front changes. The analysis of changes was performed on the selected satellite images covering the summer period (June to September) provided by the Landsat program. Then, the changes in the position of the calving front of the Jakobshavn Glacier were visualized for the period 1985–2020,with a repeatability of every 5 years. Thus, our results addressed the challenges of environmental changes to remote sensing data processing. In addition to the visualization, a surface summary of these changes was presented in the study. The results were discussed in the context of climate change data processed by means of the GIS method. Furthermore, an analysis of the effects of greenhouse gases on glacier surface changes was performed.In summary, the results reveal that satellite imagery is an excellent source of data on which to visualize glacier calving rates, comparing individual layers showing the position of the glacier calving front and calculating the area of calved ice.